Analysis Of Vocational Students' Critical Thinking Skills Using The OER-Assisted Blended Learning - Basori Basori; Sajidan Sajidan; Muhammad Akhyar; Wiranto Wiranto (Journal of Innovation in Educational and Cultural Research, 2023)
One of the competencies in 21st-century learning is critical thinking (CT). Many lessons carried out by teachers do not touch this ability because of the lack of learning innovation and the use of IT-based learning resources. This study aimed to determine and analyze the effect of using the OER (Open Educational Resources)-assisted Blended learning model on vocational students' critical thinking skills. The type of research used mixed methods with embedded design. The samples were 54 students of the Multimedia program at VHS (Vocational High School) in Surakarta, Indonesia, and the instrument used a test based on critical thinking skills, according to Facione. Quantitative data analysis used an independent t-test and the qualitative data used criteria for achieving students' critical thinking skills. The results of the study support the expectation that the BL model assisted by OER has a significant effect on student learning outcomes and that students have excellent critical thinking skills on the indicators of interpretation, analysis, evaluation, explanation, and inference.Â  On the other hand, students are weak in self-regulation.